2012
DOI: 10.1590/s0034-89102012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Validação do questionário de avaliação funcional das mãos em hanseníase

Abstract: OBJECTIVE:To validate the psychometric properties of the questionnaire on hand function assessment in leprosy. METHODS:Study conducted with a convenience sample of 101 consecutive patients in Brasília (Central-Western Brazil), from June 2008 to July 2009. The individuals were adults affected by leprosy, with impairment of the ulnar, median and radial nerves. Interobservers and intraobserver reproducibility was analyzed through successive interviews, and construct validity was analyzed through association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…The results provided evidence that the elaborated instrument has sufficient internal consistency to level analysis 13 of knowledge in basic life support of undergraduate students on the health area, indicating that it may be used as an evaluation tool. They also showed that knowledge in damage and injuries caused by hip fractures in the elderly can be isolatedly measured, which was not observed regarding risk factors.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The results provided evidence that the elaborated instrument has sufficient internal consistency to level analysis 13 of knowledge in basic life support of undergraduate students on the health area, indicating that it may be used as an evaluation tool. They also showed that knowledge in damage and injuries caused by hip fractures in the elderly can be isolatedly measured, which was not observed regarding risk factors.…”
Section: Discussionmentioning
confidence: 92%
“…The results regarding the proportion of explanation of each item in relation to the parts (between items), as well as each part regarding the entire instrument (inter-parts) are presented through values of Cronbach's alpha 13 in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We used the questionnaire developed by Ferreira et al (2012) to Evaluate the Hands Function with Nerve Lesions, especially for the involvement of the median, ulnar and radial nerves, before and after the rehabilitation program. Patient presented an improvement of the majority of the functions after the rehabilitation program (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…We used the questionnaire developed by Ferreira et al (2012) to Evaluate the Hands Function with Nerve Lesions, but numerous instruments have been proposed for the hand function evaluation in specific diseases after traumatic injuries. Among them, the most commonly used are Scale Cochin Questionnaire (Duruoz et al, 1996), ADL Questionnarie (Rosen, 2006), Green Pastures Activity Scale (Brakel et al, 1999) and Karigiri Activities of Daily Living Rating Scale (Rajkumar et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation